2000
DOI: 10.1002/pen.11286
|View full text |Cite
|
Sign up to set email alerts
|

Influence of rheological properties on the sagging of polypropylene and abs sheet for thermoforming applications

Abstract: The isothermal sagging resistance of different grades of conventional and a high melt strength (HMS) PP has been correlated with the rheological characteristics of the polymers, such as dynamic shear properties, melt strength, and zero shear viscosity. A thermoforming grade of acrylonitrile‐butadiene‐styrene (ABS) was used as a reference material. At 190°C, ABS had the highest viscosity and elastic modulus in the frequency range measured, showing that this polymer is highly elastic. HMS PP had a greater shear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 10 publications
0
32
0
Order By: Relevance
“…The figures also display multi-mode XPP and RP-S equation fits to the experimental data. Fitting parameters for the XPP and RP-S equations were tabulated earlier in Table ( [4][5][6].…”
Section: Non-linear Rheologymentioning
confidence: 99%
“…The figures also display multi-mode XPP and RP-S equation fits to the experimental data. Fitting parameters for the XPP and RP-S equations were tabulated earlier in Table ( [4][5][6].…”
Section: Non-linear Rheologymentioning
confidence: 99%
“…Wang et al [1] performed uniaxial tensile experiments using a Meissner-type rheometer to measure the properties of ABS and proposed a material model that considers the effects of strain rate, strain hardening, and temperature sensitivity. Lau et al [2] showed that ABS exhibited high resistance to sheet sag because of its high viscosity and high modulus of elasticity. Because of its broader molecular weight distribution, polypropylene had a sag resistance lower than that of ABS.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Numerical results are compared with experimental results for a simple rectangular cup. Lau et al [12] studied sagging behavior of different materials, such as polypropylene and ABS used for thermoforming. The dynamic shear test was conducted to measure viscoelastic properties, such as the storage modulus, loss modulus, and complex viscosity.…”
Section: Introductionmentioning
confidence: 99%